IMPLEMENTATION OF THE USE OF SCHOOL OPERATIONAL ASSISTANCE (BOS) FUNDS IN FULFILLING MIDDLE SCHOOL SPORTS INFRASTRUCTURE FACILITIES IN NGADIREJO DISTRICT - Handoko, Hendro; Rustiadi, Tri; Mukaromah, Siti Baitul (Journal of Physical Education and Sports, 2020)
This study aims to analyze the use of School Operational Assistance (BOS) funds to meet the needs of physical education, sports and health education facilities and analyze the availability of physical education, sports and health facilities in junior high schools in Ngadirejo District. This research was conducted through a qualitative approach with a phenomenological research design. Primary data sources were obtained from observations, interviews, and documentation. While data analysis is carried out inductively using Miles and Huberman's interactive cycle. The results showed that in Ngadirejo district, junior high schools with physical education learning facilities in the excellent category were 0 schools / by 0%, good categories by 0 schools / by 0%, fair categories were 3 schools / by 75%, poor categories were 1 School / by 25%. The allocation of the use of BOS funds in the purchase of facilities are as follows: SMP N 1 Ngadirejo amounting to Rp.6,700,000, - which is 1.7% of the total BOS funds, SMP N 2 Ngadirejo amounting to Rp. 3,463,000, - 0.92% of the total BOS funds, Ngadirejo Islamic Junior High School in the amount of Rp. 3,500,000, - 0.36% of the total BOS funds, Muhammadiyah 3 Ngadirejo Junior High School in the amount of Rp. 200,000, - that is 0.09 % of total BOS funds.